Expression analysis of antioxidant genes in response to drought stress in the fl ag leaf of two Indonesian rice cultivars - R. Refli; Sukarti Muljopawiro; Kumala Dewi; Diah Rachmawati (Universitas Gadjah Mada, 2014)
The objective of this study was to analysis the expression of antioxidant genes in response to droughtstress in Indonesian rice. The malondialdehyde (MDA) content and the expression of Cu-ZnSod1, cCu-ZnSod2,MnSod1, cApxa, cApxb, chl-sApx, Cat1, Cat2, Cat3, Gr1, Gr2, and Gr3 genes were assayed in the rice fl ag leaf ofCiherang and Situ Bagendit cultivars subjected to control, mild and severe drought during the grain fi llingphase. Increase in MDA content of Ciherang treated to mild and severe drought was almost two-fold andthree-fold respectively, while MDA content in Situ Bagendit subjected to mild and severe drought increasedapproximately one-fold and two-fold as compared to the control. The semi quantitative reverse transcriptionpolymerase chain reaction (sqRT-PCR) analysis showed that the expression of cCu-ZnSod1, MnSod1, Cat2, Gr3genes of Ciherang, and cCu-ZnSod2, MnSod1, cApxa, cApxb, chl-sAPX, Cat2 and Gr1 genes of Situ Bagendit increasedin fl ag leaf of plant treated to drought. Expressions of cApxb, chl-sApx, Cat3 of Ciherang and Cu-ZnSod1 and Gr2genes of Situ Bagendit were not changed signifi cantly by drought stress. Decreased expression was shownby cCu-ZnSod2, cApxa, Cat1, Gr1 and Gr2 genes of Ciherang, and Cat1, Cat3 and Gr3 genes of Situ Bagendit. Theresults indicated that the activity of oxidative defense was regulated by four genes; cCu-ZnSod1, MnSod1, Cat2,Gr3 in Ciherang, and eight genes; cCu-ZnSod1, cCu-ZnSod2, MnSod1, cApxa, cApxb, chl-sApx, Cat2 and Gr1 in SituBagendit. Therefore, differences in the number of antioxidant genes controlling oxidative defense systemmight determine the difference of the oxidative defense capacity between both cultivars in response to droughtstress during grain fi lling.